2018
DOI: 10.3389/fneur.2018.00132
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Limbic System Mapping of Main Cognitive Domains in Multiple Sclerosis

Abstract: Background and objectiveCognitive impairment (CI) is common in multiple sclerosis (MS), but underlying mechanisms and their imaging correlates are not completely understood. The gray and white matter structures of the limbic system (LS) play crucial roles in different aspects of cognition. To investigate their role in MS related CI, and since a detailed evaluations are lacking in the literature, we used a comprehensive neuroimaging approach to evaluate CI’s correlations with the main components of the LS.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
2
11
0
2
Order By: Relevance
“…21 However, later it was shown to contribute to the neural basis of learning and memory. 4 Additionally, recent MS studies showing the importance of the amygdala and OFC 10,22 in cognition support our findings.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…21 However, later it was shown to contribute to the neural basis of learning and memory. 4 Additionally, recent MS studies showing the importance of the amygdala and OFC 10,22 in cognition support our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Yakovlev described the circuit of orbitofrontal cortex-dorsomedial thalamus-amygdala as basolateral limbic circuit in addition to Papez circuit. 3 This circuit has two main white matter loops; 1) anteriorly uncinate fasciculus, previously studied in MS related CI 1011 connecting amygdala or temporal pole to orbitofrontal frontal cortex and 2) posteriorly bisynaptic orbitofrontoamygdalar loop including bidirectional and ipsilateral orbitfrontothalamic and amygdalothalamic projection pathways. From the cortex, this loop arises from OFC travels posteriorly through the anterior limb of the internal capsule and synapses in the dorsomedial nucleus of the thalamus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, these studies showed patterns of reduced left lateralization when verbal fluency tasks were performed by patients with Alzheimer’s disease, epilepsy and schizophrenia (Weiss et al, 2004; Metternich et al, 2014; Rodríguez-Aranda et al, 2016). A recent study, focusing primarily on the limbic system in MS patients, showed associations between verbal fluency and the UF, bilaterally, and in particular, an association between category-based fluency and the right UF (Keser et al, 2018). The correlation we found in the right IFOF, a neighboring right hemispheric ventral pathway, aligns with this overall tendency for reduced left lateralization in clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…Still, this finding provides supporting evidence for the involvement of the ventral tracts in morphological processing sampled with production tasks. Other studies reported associations between letter-or categorybased fluency and properties of several white matter tracts, in clinical patients suffering from multiple sclerosis, aphasia or stroke (Blecher et al, 2019;Griffis et al, 2017;Keser et al, 2018;Li et al, 2017; but see Vallesi and Babcock (2020) for null results in healthy adults). Morpheme-based fluency may be more challenging than standard fluency tasks, as it requires using metalinguistic knowledge for lexical search and applying more restrictive response selection criteria.…”
Section: Morpheme-based Fluency Is Associated With Ventral and Dorsalmentioning
confidence: 99%